Recent Advances in Biosensors Based on Conducting Polymers for Biomedical Applications - Acar, Tugba; Cimen, Kuebra Nur; Ozalp, Elif; Ilica, Oeznur; Ozerol, Esma Ahlatcioglu (WILEY-V C H VERLAG GMBH, 2023)
Biosensors are very crucial applications in the medical field because of their stability, selectivity, sensitivity, reproducibility and linearity. Conducting polymers (CPs), which stand out with their electrical conductivity and easily synthesize and process, are used to improve the properties of biosensors. CPs are organic materials preferred in biosensor use because of both electrical and optical properties, biocompatible, thermal and environmental stability. In this review, a detailed analysis of the literature on biosensors based on conductive polymers and their biomedical applications has been made. It has been presented that conductive polymer-based biosensors have an important role in biomedical applications.
Keywords: Biosensors; PEDOT; Polyaniline; Polypyrrole; Polythiophene; OXIDE; PHTHALOCYANINE; Chemistry